Mastering GitLab 12 : implement DevOps culture and repository management solutions - Evertse, Joost (Packt Publishing, 2019)
GitLab is an open source end-to-end software development platform with built-in version control, issue tracking, code review, CI/CD, and more. This book will help you master the software development workflow in GitLab and boost your productivity by putting teams to work on GitLab via an on premise installation or via a Cloud-based infrastructure.